Islamic entrepreneurship inclination: a conceptual study using Systematic Literature Review (SLR) / Nurjannah Salleha ... [et al.] - Salleha, Nurjannah; Md Jani, Syahrina Hayati; Mohd Ali, Nor Aishah; Salleh, Aisyah Wahyuna (Center for Islamic Philantrophy & Social Finance (CIPSF), 2020)
Till now, entrepreneurship is commonly clarified as an individually focused economic undertaking (Al-Dajani & Marlow, 2013). Since, entrepreneurship plays an important role in economic development (Zhang et al., 2014), understanding the role of entrepreneurship in the economic process requires the decomposition of the concept of entrepreneurship itself. Besides, one of the key issues in the economy related to growth and development is entrepreneurship (Toma et al., 2014). Therefore, sustaining entrepreneurship can become a powerful tool to develop capacity at global and individual levels. Despite that, entrepreneurship will also be able to promote a higher level of economic development. Economic development has always been seen to correlate with wealth distribution or undisbursed wealth that causes poverty. It is recommended to manage the distribution of wealth so that the problems relating to economic development would be reduced. Thus, entrepreneurship in higher education institution (HEIs) is established to develop high impact, low cost, and rapidly executed programs to contribute to the two aforementioned impact areas.